Pengaruh Pengetahuan Keuangan Dan Pengetahuan Kewirausahaan Terhadap Kinerja Bisnis UMKM Kuliner Saji Di Kota Padang - Utami, Vindora Febilanda; Nurningsih, Sari; Saputra, Syailendra Eka (CV. ITTC INDONESIA, 2024)
This research aims to empirically prove the influence of financial knowledge and entrepreneurial knowledge on the business performance of culinary food MSMEs in Padang City. Apart from that, this research also aims to prove the role of financial knowledge in strengthening the relationship between entrepreneurial knowledge and MSME business performance in Padang City. This research was carried out on all food culinary MSMEs spread across the city of Padang, but only 104 culinary business owners and operators in the city of Padang were used as samples. The analysis method was carried out using purposive sampling technique. Data collection was carried out by surveying owners and operators of culinary MSMEs in Padang City. The data analysis method used is multiple regression (OLS). In accordance with the description of the analysis and discussion that has been carried out, it can be concluded that entrepreneurial knowledge has a positive and significant effect on the performance of the culinary food MSME business in Padang City. Apart from that, from the results of hypothesis testing, it can be proven that financial knowledge has a positive and significant effect on the performance of the culinary food MSME business in Padang City. In the description of the results of hypothesis testing, it was also found that financial knowledge was able to strengthen the relationship between entrepreneurial knowledge and business performance in culinary food MSMEs in Padang City.